Development of an actinium-225 radioimmunoconjugate for targeted alpha therapy against SARS-CoV-2. (7th July 2022) - Pallares, Roger M.; Flick, Matthew; Shield, Katherine M.; Bailey, Tyler A.; Velappan, Nileena; Lillo, Antonietta M.; Abergel, Rebecca J.
Abstract : Cytotoxicity was induced in cells mimicking SARS-CoV-2 infection by a 225 Ac-radiolabeled antibody that targets the RBD2 of the spike protein. Abstract : Targeted alpha therapy offers unique opportunities for the treatment of tumours and infections. Here, we report the development of a new radioimmunoconjugate construct that targets SARS-CoV-2 infected cells, which act as viral reservoirs and promote virus replication and infection spread. The chosen antibody selectively binds to the ACE2-receptor binding domain of the spike protein, and prevents the protein binding to the receptor. Furthermore, the antibody has been radiolabelled with 225 Ac, and the therapeutic performance of the resulting radioimmunoconjugate has been demonstrated in vitro against cells mimicking SARS-CoV-2 infection.